The application of laws of conservation of energy and momentum during trenchless horizontal laying of communications - D. I. Chernyavsky; D. D. Gapon (Омский научный вестник)
An engineering technique is proposed for calculating the technical parameters of a pneumatic hammer for horizontal clogging of steel pipes into the foundation of roads for the laying of various communications – electrical cables, communication lines, sewerage, etc. The method is based on the use of equation of laws of conservation of energy and momentum. Examples of horizontal clogging of pipes in a compressible soil are considered. The concept of «additional mass» is introduced taking into account the friction force of the soil the pipe. This value is added to the weight of the pipe. This makes it possible to estimate the efficiency of the transport of kinetic energy from the hammer to the pipe as penetration of the pipe into the ground increases.